Effect of training surface on acute physiological responses after interval training - Binnie, M. J.; Dawson, B.; Pinnington, H.; Landers, G.; Peeling, P. (The Journal of Strength and Conditioning Research, 2013)
This study compared the effect of sand and grass training surfaces during a common preseason interval training session in well-trained team sport athletes (n = 10). The participants initially completed a preliminary testing session to gather baseline (BASE) performance data for vertical jump, repeated sprint ability, and a 3-km running time trial (RTT). Three days subsequent to BASE, all the athletes completed the first interval training session, which was followed by a repeat of the BASE performance tests the following day (24 hours postexercise). Seven days later, the same interval training session was completed on the opposing surface and was again followed 24 hours later by the BASE performance tests. During each session, blood lactate (BLa), ratings of perceived exertion, and heart rate (HR) were recorded. Additionally, venous blood was collected preexercise, postexercise, and 24 hours postexercise and analyzed for serum concentrations of myoglobin, creatine kinase, haptoglobin, and C-reactive protein. Results showed significantly higher BLa and HR responses experienced during the SAND session (p < 0.05), with no differences observed between surfaces for the blood markers of muscle damage, inflammation, and hemolysis (p > 0.05). Twenty-four hours later, the RTT was performed significantly faster after the SAND session compared with GRASS (p = 0.001). These results suggest that performing interval training on a sand (vs. grass) surface can result in a greater physiological response, without any additional detriment to next day endurance performance.